Pengaruh Kekerasan Terhadap Kesehatan Psikologis Anak - Nabila Fitriani; Asep Suherman (CV. ITTC INDONESIA, 2024)
This research aims to explore the impact of violence on children's psychological health and emphasizes the importance of early intervention in the context of child protection in Indonesia, in accordance with Law Number 35 of 2014 concerning Child Protection. The method used is normative juridical research with a doctrinal approach, which involves collecting and analyzing secondary data from various legal sources, including laws, official documents and related literature. The research results show that violence against children, whether physical, verbal or emotional, has a significant impact on children's mental health, causing psychological disorders such as anxiety and depression. Even though there is a clear legal framework, its implementation is still hampered by cultural factors, social stigma, and low levels of reporting of cases of violence. This research recommends the need to increase public awareness regarding the impact of violence as well as more effective law enforcement, including training for health workers and education for parents, so that children can grow up in a safe environment and support their psychological health.